On the crisis of modernity. A reading from the perspective of art - Malquori, Diego (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
In this article I propose a reflection on art as an expression of the redefinition of modern culture. Art, in effect, expresses the lines that define the world, but at the same time produces a different form of truth. That is why a discourse on art cannot ignore an analysis of the world in which it originates and that somehow it tries to express. In this direction, three readings of the question of modernity are considered: the Dialectic of Enlightenment by Horkheimer and Adorno, Barbarism by Henry, and The End of Modernity by Vattimo. In the second part, the discourse focuses on the manifestation of the crisis in art, trying to offer other meanings, from different philosophical approaches, to the transition from modernity to postmodernity.